Pterostilbene Attenuates Astrocytic Inflammation and Neuronal Oxidative Injury After Ischemia-Reperfusion by Inhibiting NF-κB Phosphorylation - Liu, Haixiao; Wu, Xun; Luo, Jianing; Wang, Xiaogang; Guo, Hao; Feng, Dayun; Zhao, Lei; Bai, Hao; Song, Mingyang; Liu, Xunyuan; Guo, Wei; Li, Xia; et al. (Frontiers in Immunology, 2019)
Astrocyte-mediated inflammation and oxidative stress elicit cerebral ischemia-reperfusion (IR) injury after stroke. Nuclear factor (NF)-κB activates astrocytes and generates pro-inflammatory factors. The purpose of the present study is to elucidate the effect of pterostilbene (PTE, a natural stilbene) on astrocytic inflammation and neuronal oxidative injury following cerebral ischemia-reperfusion injury. A middle cerebral artery occlusion-reperfusion (MCAO/R) mouse model and HT22/U251 co-culture model subjected to oxygen-glucose deprivation and re-introduction (OGD/R) were employed, with or without PTE treatment. The data showed that PTE delivery immediately after reperfusion, at 1 h after occlusion, decreased infarct volume, brain edema, and neuronal apoptosis and improved long-term neurological function. PTE decreased oxidation (i.e., production of reactive oxygen species, malondialdehyde) and inflammatory mediators (tumor necrosis factor-α, interleukin-1β, and interleukin-6) and increased anti-oxidative enzyme activities (i.e., of superoxide dismutase, glutathione peroxidase), by inhibiting phosphorylation and nuclear translocation of NF-κB. In conclusion, PTE attenuated astrocyte-mediated inflammation and oxidative injury following IR via NF-κB inhibition. Overall, PTE is a promising neuroprotective agent.